About of the necessity of the modification of the nuclear chronometry methods in astrophysics and geophysics - Olkhovsky, V.S.; Dolinska, M.E.; Doroshko, N.L. (Вопросы атомной науки и техники, 2009)
In practically all known till now methods of nuclear chronometry there were usually taken into account the life-times of only fundamental states of a-radioactive nucleus. But in the processes of nuclear synthesis in stars and under the influence of the constant cosmic radiation on surfaces of planets the excitations of the a-radioactive nuclei are going on. Between them there are the states with the excited a-particles inside the parent nuclei and so with much smaller life-times. And inside the large masses of stellar, terrestrial and meteoric substances the transitions between different internal conditions of radioactive nuclei are accompanied by infinite chains of the g-radiations with the subsequent g-absorptions, the further g-radiations etc. For the description of the a-decay evolution with considering of such excited states and multiple g-radiations and g-absorptions inside stars and under the influence of the cosmic radiation on the earth surface we present the quantum-mechanical approach, which is based on the generalized Krylov-Fock theorem. Some simple estimations are also presented. They bring to the conclusion that the usual (non-corrected) "nuclear clocks" do really indicate not to realistic values but to the upper limits of the durations of the a-decay stellar and planet processes. В практично відомих досі методах ядерної хронометрії звичайно враховувалися часи життя лише основних станів радіоактивних ядер. Але, як відомо, при нуклеосинтезі утворюється багато збуджених станів радіоактивних ядер-хронометрів із значно меншим часом життя. При переходах між різними внутрішніми станами радіоактивних ядер, що знаходяться в тепловому русі всередині великих мас зоряних, земних і метеоритних речовин, поряд з g-випроміненням існують нескінченні ланцюжки g-поглинань, наступних g-випромінень, подальших g-поглинань і.т.д. Для опису еволюції розпаду з врахуванням цих факторів в наших попередніх роботах було запропоновано квантово-механічний підхід, який базується на узагальненій нами теоремі Крилова-Фока. В цій роботі наведені подальше уточнення попередніх оцінок і розрахунків та конкретно сформульовані подальші етапи розвитку нашого підходу і проведення наступних розрахунків з урахуванням ефекту Допплера при наявності теплового руху радіоактивних ядер, ефекту відбиття при g-випроміненнях і g-поглинаннях та впливу постійно присутнього космічного випромінювання на формування збуджених станів ядер-хронометрів та зміну їхньої кінетичної енергії на поверхні Землі. В практически известных методах ядерной хронометрии обычно учитывались времена жизни только основных состояний радиоактивных ядер. Но, как известно при нуклеосинтезе образуется много возбужденных состояний радиоактивных ядер-хронометров со значительно меньшим временем жизни. При переходах между разными внутренними состояниями радиоактивных ядер, которые находятся в тепловом движении внутри больших масс звездных, земных и метеоритных веществ, рядом с g-излучением существуют бесконечные цепочки g-поглощений, последующих g-излучений, дальнейших g-поглощений и.т.д. Для описания эволюции распада с учетом этих факторов в наших предыдущих работах был предложен квантово-механический подход, который базируется на обобщенной нами теореме Крылова-Фока. В этой работе приведено дальнейшее уточнение предыдущих оценок и расчетов, а также конкретно сформулированы дальнейшие этапы развития нашего подхода и проведения дальнейших расчетов с учетом эффекта Допплера при наличии теплового движения радиоактивных ядер, эффекта выбивания при g-излучениях и g-поглощениях, а также влияния постоянно присутствующего космического излучения на формирование возбужденных состояний ядер-хронометров и изменение их кинетической энергии на поверхности Земли.